Role of Ultrasonography in Evaluation of Various Causes of Pelvic Pain in First Trimester of Pregnancy - Mehwish Waqar, Zaeema Ali, Abdul Majeed Khan, Asma Afzal Kiani, Shafaath Husain Syed Mohammed, Nadeem Akram Butt, (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: Acute pelvic pain during pregnancy can be challenging to identify and manage. Ultrasound is still the most often utilized imaging modality for pregnant and postpartum women. The present study aimed to evaluate the ultrasonography role in various causes of pelvic pain in first trimester of pregnancy. Patients and Methods: This descriptive cross-sectional study was carried out on 286 pelvic pain pregnant women of first trimester. It was conducted in the department of Radiology in collaboration with Obstetrics and Gynecology department of Jinnah Hospital, Lahore from March 2022 to November 2022. Pregnant women with pelvic pain during early pregnancy were enrolled. Patient’s demographic details i.e. age, gestational age, HC, molar pregnancy, CRL, Fibroid, FHR, and bleeding on ultrasound were recorded. Data analysis was done using SPSS version 27. . Results: The overall mean age of participants was 26.84±2.86 years (18 to 45 years). Patients distribution based on age were as follows: 76 (26.6%) in 18-25 years, 156 (54.5%) in 26-35 years, and 54 (18.9%) in 36-45 years. Out of the total 286 pregnant women, the prevalence of bleeding, fibroids, cyst, and ectopic pregnancy was 92 (32.2%), 42 (14.7%), 56 (19.6%), and 18 (6.3%) respectively. The prevalence of pelvic pain causes such as Corpus luteal cyst, Dermoid Cyst, Ectopic pregnancy, Intramural Fibroid, Submucosal Fibroid, and sub serosal fibroid was 38/54 (70.4%), 26/34 (76.5%), 22/28 (78.6%), 1/20 (5%), 4/10 (40%), and 1/22 (4.5%) respectively. Conclusion: Bleeding was the most dominant finding followed by cyst and fibroids in pregnant women with chronic pelvic pain during early pregnancy. Pelvic pain in the early pregnancy can be difficult to treat. In assessing these individuals, ultrasound is a critical imaging modality. Keywords: Pelvic pain, ultrasonography, causes, first trimester, pregnancy